2002
DOI: 10.1046/j.1365-2125.2002.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and electrocardiographic pharmacodynamics of artemether‐lumefantrine (Riamet®) with concomitant administration of ketoconazole in healthy subjects

Abstract: Aims To evaluate whether the potent CYP3A4 inhibitor ketoconazole has any influence on the pharmacokinetic and electrocardiographic parameters of the antimalarial co-artemether (artemether-lumefantrine) in healthy subjects. Methods Sixteen subjects were randomized in an open-label, two period crossover design study. Subjects received a single dose of co-artemether (day 1) either alone or in combination with multiple oral doses of ketoconazole (400 mg on day 1 followed by 200 mg o.d. for 4 additional days). Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
45
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 44 publications
8
45
3
Order By: Relevance
“…However, malaria illness could attenuate the autoinduction seen in our clinically well HIV-infected patients and in previously described studies on healthy volunteers. Artemether and dihydroartemisinin exposure in our ART-naïve group is similar to previously published results in healthy volunteer studies (15,21), suggesting that there is not a marked HIV disease effect.…”
Section: Discussionsupporting
confidence: 80%
“…However, malaria illness could attenuate the autoinduction seen in our clinically well HIV-infected patients and in previously described studies on healthy volunteers. Artemether and dihydroartemisinin exposure in our ART-naïve group is similar to previously published results in healthy volunteer studies (15,21), suggesting that there is not a marked HIV disease effect.…”
Section: Discussionsupporting
confidence: 80%
“…Artemether is metabolized by the cytochrome P450 (CYP450) enzymes CYP1A2, CYP2B6, CYP2C19, and CYP3A4 in vitro (38); but no contribution by CYP2C19 could be seen in healthy volunteers (48). Lumefantrine is mainly metabolized by CYP3A4 (26)(27)(28). In vitro studies have shown that CYP2A6 is the most important CYP450 enzyme in the metabolism of nicotine (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of AM to DHA is catalyzed by cytochrome P450 (P450) (van Agtmael et al, 1999b,c;Navaratnam et al, 2000). However, the elimination half-life of AM is very short, and it shows large interindividual variability in pharmacokinetic parameters (Na Bangchang et al, 1994;Mordi et al, 1997;van Agtmael et al, 1999a;Lefèvre et al, 2002;Ali et al, 2010;Mwesigwa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%